2022
DOI: 10.1590/0034-7167-2021-0640
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the temporal trend of mortality from sickle cell anemia in Brazil

Abstract: Objectives: To analyze the temporal trend of mortality from sickle cell anemia in Brazil, by region, in the period 1997-2017. Methods: epidemiological study, with an ecological design, with a temporal trend, carried out with data from the Mortality Information System. For descriptive analysis, absolute and relative frequencies were used. In the correlation analysis, the ANOVA test was used, followed by Tukey’s post-test. The temporal trend was obtained using the cubic polynomial regression test. Results: 6,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…The first Brazilian single institutional study in 2017 showed that the mortality rate was 18.87% among adult SCD patients 23 . Further, combined data between 1997 and 2017, from Brazil showed that mortality was more in the males (50.4%), and patients aged between 25 and 34 years had a higher incidence of deaths 24 . In another study from Brazil between 2000 and 2018, during the entire period the mean ages at death is significantly lower for males, than for females, being 29.4 (± 19.6) versus 33.3 (± 20.3) years respectively 25 .…”
Section: Discussionmentioning
confidence: 94%
“…The first Brazilian single institutional study in 2017 showed that the mortality rate was 18.87% among adult SCD patients 23 . Further, combined data between 1997 and 2017, from Brazil showed that mortality was more in the males (50.4%), and patients aged between 25 and 34 years had a higher incidence of deaths 24 . In another study from Brazil between 2000 and 2018, during the entire period the mean ages at death is significantly lower for males, than for females, being 29.4 (± 19.6) versus 33.3 (± 20.3) years respectively 25 .…”
Section: Discussionmentioning
confidence: 94%
“…123 patients (82 males, 41 females) who were enrolled in the study had a median age (IQR) of 27 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years, with a range between 1.5 to 79 years. Painful VOC episodes > 6/year were seen in almost one-fth of this cohort (17.9%), while most patients had a signi cant past history of SCD-related complications including ACS (52.8%), splenic sequestration (21.1%), right upper quadrant syndrome (19.5%) and stroke (13.8%) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“… 10 Mota et al analyzed data from 1997–2017 and observed a higher incidence of deaths between the ages of 25 and 34 years. 24 …”
Section: Discussionmentioning
confidence: 99%